Effective knowledge translation approaches and practices in Indigenous health research: a systematic review protocol. Issue 1 (December 2017) - Morton Ninomiya, Melody; Atkinson, Donna; Brascoupé, Simon; Firestone, Michelle; Robinson, Nicole; Reading, Jeff; Ziegler, Carolyn; Maddox, Raglan; Smylie, Janet
Abstract Background Effective knowledge translation (KT) is critical to implementing program and policy changes that require shared understandings of knowledge systems, assumptions, and practices. Within mainstream research institutions and funding agencies, systemic and insidious inequities, privileges, and power relationships inhibit Indigenous peoples' control, input, and benefits over research. This systematic review will examine literature on KT initiatives in Indigenous health research to help identify wise and promising Indigenous KT practices and language in Canada and abroad. Methods Indexed databases including Aboriginal Health Abstract Database, Bibliography of Native North Americans, CINAHL, Circumpolar Health Bibliographic Database, Dissertation Abstracts, First Nations Periodical Index, Medline, National Indigenous Studies Portal, ProQuest Conference Papers Index, PsycInfo, Social Services Abstracts, Social Work Abstracts, and Web of Science will be searched. A comprehensive list of non-indexed and grey literature sources will also be searched. For inclusion, documents must be published in English; linked to Indigenous health and wellbeing; focused on Indigenous people; document KT goals, activities, and rationale; and include an evaluation of their KT strategy. Identified quantitative, qualitative, and mixed methods' studies that meet the inclusion criteria will then be appraised using a quality appraisal tool for research with Indigenous people. Studies that score 6 or higher on the quality appraisal tool will be included for analysis. Discussion This unique systematic review involves robust Indigenous community engagement strategies throughout the life of the project, starting with the development of the review protocol. The review is being guided by senior Indigenous researchers who will purposefully include literature sources characterized by Indigenous authorship, community engagement, and representation; screen and appraise sources that meet Indigenous health research principles; and discuss the project with the Indigenous Elders to further explore the hazards, wisdom, and processes of sharing knowledge in research contexts. The overall aim of this review is to provide the evidence and basis for recommendations on wise practices for KT terminology and research that improves Indigenous health and wellbeing and/or access to services, programs, or policies that will lead to improved health and wellbeing. Systematic review registration PROSPEROCRD42016049787 .